Fetal MRI - Prayer, Daniela; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This is the most comprehensive book to be written on the subject of fetal MRI. It provides a practical hands-on approach to the use of state-of-the-art MRI techniques and the optimization of sequences. Fetal pathological conditions and methods of prenatal MRI diagnosis are discussed by organ system, and the available literature is reviewed. Interpretation of findings and potential artifacts are thoroughly considered with the aid of numerous high-quality illustrations. In addition, the implications of fetal MRI are explored from the medico-legal and ethical points of view. This book will serve as a detailed resource for radiologists, obstetricians, neonatologists, geneticists, and any practitioner wanting to gain an in-depth understanding of fetal MRI technology and applications. In addition, it will provide a reference source for technologists, researchers, students, and those who are implementing a fetal MRI service in their own facility.
History of Fetal MRI -- Indications for Fetal MRI -- Ethics of Fetal MRI -- How to Shorten MR Sequences -- Fetal MRI at Higher Field Strength -- Fetal MRI Safety -- The Psychic State of the Pregnant Woman and Prenatal Diagnostic -- Methods of Fetal MRI -- Histology of Normal Fetal Brain Development -- Normal Brain Development at High Field in Vitro -- Normal Fetal In-Vivo Brain Development on MRI -- Metabolic Brain Development -- Phylogeny and Ontogeny of Early Fetal Behavior -- Fetal Neurology -- Ultrasound and MRI of the Fetal Brain, Pros and Cons -- MRI of Normal Fetal Lung.-MRI of the Fetal Skeleton -- MRI of the Fetal Heart -- MRI of the Fetal Endocrine Glands.-Fetal MRI of Facial Clefts -- Cerebral Malformations -- Cerebral Acquired Disease -- Diagnosis of Congenital Diaphragmatic Hernia -- Anesthesia in Fetal Surgery -- Treatment of Congenital Diaphragmatic Hernia -- MRI of the Pathological Fetal Thorax -- MRI of the Fetal Abdomen -- Normal and Pathological Placental Development: MRI and Pathology -- Problems of Multiplet Pregnancies Ultrasound and MRI -- Treatment of Fetofetal Transfusion Syndrome -- Pathological Correlation of Prenatal Findings -- Postmortem Fetal MRI -- Genetics of Fetal Disease -- Maternal Diseases with Possible Impact on Pegnancy.
Keywords: Medicine; Obstetrics; Radiology, Medical; Neurosurgery; Pediatrics; Surgery; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Obstetrics/Perinatology.; Pediatric Surgery; Pediatrics; Neurosurgery